Exploring the enigma of low prevalence of post-traumatic stress disorder in India - Ateev S. Chandna; Satish Suhas; Rahul Patley; Damodharan Dinakaran; Narayana Manjunatha; Girish N. Rao; Gopalkrishna Gururaj; Mathew Varghese; Vivek Benegal; NMHS National Collaborators Group (Indian Journal of Psychiatry)
Introduction: Post-traumatic stress disorder (PTSD) is a chronic psychiatric condition associated with significant distress and dysfunction. While worldwide estimates of prevalence range from 3.9% to 24%, little research has been conducted to identify the prevalence of PTSD in the general population of India. This study analyzes data from the National Mental Health Survey 2015-2016, a comprehensive epidemiological study of mental health disorders in India, to explore the unique characteristics and prevalence of PTSD in the Indian population. Materials and Methods: The National Mental Health Survey 2015-2016 employed a multiple-stage, stratified, cluster-sampling methodology, covering 39,532 individuals in 12 states of India. The Mini-International Neuropsychiatric Interview (MINI) version 6.0.0 was used to diagnose psychiatric disorders, including PTSD. A detailed analysis of sociodemographic profiles, prevalence patterns, comorbidities, economic and social impact, and treatment-seeking behavior was conducted. Firth penalized logistic regression was employed to identify associated sociodemographic factors. Results: The study revealed a low prevalence of PTSD in India at 0.2%, significantly lower than global averages. Factors associated with PTSD included female gender, middle age (40-49 years), and urban residence. The study also highlighted a high rate of comorbid mood and anxiety disorders, substantial disability, poor treatment-seeking behavior, and significant suicidal risk among individuals with PTSD. Conclusion: Our findings underscore the need for culturally informed diagnostic and management programs to accurately identify and address PTSD in the Indian population. Cultural nuances, stigma, and the use of Western-derived diagnostic instruments likely contribute to the underidentification and undertreatment of PTSD in India. The study emphasizes the importance of recognizing and addressing these challenges to improve mental health outcomes in India.